2007
DOI: 10.1021/om061057i
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Formation of Organyl(oxo)boranes (RBO) (R = C6H5or CH3) from Boroxins ((RBO)3):  A Matrix Isolation Study

Abstract: Flash vacuum pyrolysis of triphenyl- and trimethylboroxin and subsequent trapping of the gas phase products in a large excess of argon at T < 20 K allows matrix isolation and characterization by IR spectroscopy of phenyl(oxo)borane and methyl(oxo)borane. The nature of the matrix isolated species, monomeric CH3BO, 1:1 dimer complex of CH3BO, (CH3BO)2, and (CH3BO)3, depends strongly on the trapping temperature and matrix host gas (Ar vs Xe) with the boroxin dominating at 30 K (Ar) or 55 K (Xe). An ab initio inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 51 publications
(65 reference statements)
0
37
0
1
Order By: Relevance
“…All signals of 4 disappear simultaneously while new signals in the range 2305 – 2236 cm −1 of the isocyanate group of 8 and the signals 1965 and 2208 cm −1 of the BO unit [14] appear (Figure 2). The structure of 8 could be confirmed again through use of isotopically labelled carbon dioxide and is in excellent agreement with the corresponding computed isotopic shifts (B3LYP/6-311+G**, Supporting Information Table S4).…”
mentioning
confidence: 99%
“…All signals of 4 disappear simultaneously while new signals in the range 2305 – 2236 cm −1 of the isocyanate group of 8 and the signals 1965 and 2208 cm −1 of the BO unit [14] appear (Figure 2). The structure of 8 could be confirmed again through use of isotopically labelled carbon dioxide and is in excellent agreement with the corresponding computed isotopic shifts (B3LYP/6-311+G**, Supporting Information Table S4).…”
mentioning
confidence: 99%
“…14−16 However, oxoboranes are very reactive due to the highly polar boron−oxygen bond and readily form oligomers to compensate for their intrinsic electron deficiency. 17,18 As a result, the dehydration of boronic acids lead to the formation of oligomers of oxoborane instead of monomers. 17 Further, Bock et al reported the synthesis of methyloxoborane (CH 3 BO) via thermolysis of methyl-1,3,2-diborolane-4,5-dione, but the product promptly underwent cyclo-oligomerization to (CH 3 BO) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…17,18 As a result, the dehydration of boronic acids lead to the formation of oligomers of oxoborane instead of monomers. 17 Further, Bock et al reported the synthesis of methyloxoborane (CH 3 BO) via thermolysis of methyl-1,3,2-diborolane-4,5-dione, but the product promptly underwent cyclo-oligomerization to (CH 3 BO) 3 . 19 The cyclo-oligomerization of RBO can be observed even at temperatures as low as 50 K; 17 isolated oxoboranes were reported either as reactive intermediates or in cryogenic matrices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, these anhydrides of boronic acids were assigned cyclotrimeric structures. [7] However, considerable experimental efforts are necessary to obtain a glance at the elusive methyloxoborane or its cyclodimerization product (MeBO) 2 , as the trimer (MeBO) 3 is the predominant species even at very low trapping temperatures of 50 K. In contrast, sterically demanding substituents favor the formation of cyclodimeric structures. [2] The simplest derivative (HBO) 3 (1, Figure 1) was identified as the product of different high energetic redox processes, [3] and the monomeric counterpart HBO could be observed spectroscopically under similar reaction conditions, either in the gas phase [4] or in lowtemperature matrix isolation studies.…”
mentioning
confidence: 99%